Development of Coastal Tourism Objects in Increasing Pad Banggai Laut Regency - Siti Fazryanti Rahmad (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to describe the strategy for developing beach tourism objects and analyze their contribution to increasing Regional Original Income (PAD) in Banggai Laut Regency. Methodology: This research used a descriptive qualitative method with purposive sampling. Data were obtained through observation, interviews, and documentation at the Department of Tourism, Banggai Laut Regency. Informants consisted of five individuals who were directly involved in tourism development and PAD management. Main Findings: The development strategy includes coordination with tourism stakeholders, destination development, tourism marketing, and collaboration with tourism institutions. Contributions to PAD are derived from hotel tax, restaurant tax, entertainment tax, and special parking fees. Tourism activities significantly support local financial independence and economic growth in Banggai Laut Regency. Novelty/Originality of this study: This study offers a contextual insight into how underutilized coastal tourism potential can be strategically developed to boost PAD. It highlights an integrated tourism development model involving local government collaboration and public-private synergy, which can serve as a reference for similar coastal regions in Indonesia.